A pragmatist approach to the hope discourse in health care research. (18th February 2014) - Herrestad, Henning; Biong, Stian; McCormack, Brendan; Borg, Marit; Karlsson, Bengt
Abstract Hope is a central concept in nursing and other fields of health care. However, there is no consensus about the concept of hope. We argue that seeking consensus is futile given the multifaceted and multidimensional nature of the concept, but instead we encourage in‐depth studies of the assumptions behind talk about hope in specific contexts. Our approach to the 'science of hope' is inspired by philosophical pragmatism. We argue that hope is a concept that opens different rooms for action in different contexts and that accordingly, all hope interventions are contextually sensitive. Careful attention to how the relative positions and power of nurses and patients influence what can be inferred from their different ways of talking about hope may make hopeful conversations more meaningful in health care relationships.